Disinfection of Viruses 2022
DOI: 10.5772/intechopen.101752
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Coatings as Continuously Active Disinfectants

Abstract: Antimicrobial surfaces and coatings have been available for many decades and have largely been designed to kill or prevent the growth of bacteria and fungi. Antiviral coatings have become of particular interest more recently during the COVID-19 pandemic as they are designed to act as continuously active disinfectants. The most studied antiviral coatings have been metal-based or are comprised of silane quaternary ammonium formulations. Copper and silver interact directly with proteins and nucleic acids, and inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…This becomes particularly critical as surfaces tend to become re-contaminated over time, which was simulated by the regular re-inoculations performed in the current study. While previous research efforts have demonstrated the effectiveness of self-disinfecting surfaces, most of the actives studied were embedded materials comprised, in part, of titanium dioxide, metals, or novel specialized polymers that were under development and not broadly available for commercial use (Querido et al, 2019; Ikner et al, 2021; Ikner and Gerba, 2021). Published studies employing wear and abrasion with repeated reinoculations to assess the residual efficacy of spray products are scant (Rutala et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This becomes particularly critical as surfaces tend to become re-contaminated over time, which was simulated by the regular re-inoculations performed in the current study. While previous research efforts have demonstrated the effectiveness of self-disinfecting surfaces, most of the actives studied were embedded materials comprised, in part, of titanium dioxide, metals, or novel specialized polymers that were under development and not broadly available for commercial use (Querido et al, 2019; Ikner et al, 2021; Ikner and Gerba, 2021). Published studies employing wear and abrasion with repeated reinoculations to assess the residual efficacy of spray products are scant (Rutala et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, traditional chemical-based disinfectants are still primarily in use. However, nano-based formulations represent a promising field of research and will assist in control of current and similar viral outbreaks in the future [99].…”
Section: Nanotechnology-based Formulations For Sars-cov-2 Controlmentioning
confidence: 99%